Peningkatan Kepercayaan Diri Dengan Menerapkan Model Pembelajaran Take and Give - Nanik Yayuk (Departement of Mathematics Education, 2021)
This study aims to increase students' confidence in learning by applying the Take and Give learning model. The subjects of this study were 27 students of class 1-A with the research location at SD Negeri Wonokusumo VI / 45 Surabaya. The research was conducted with a two-cycle action mechanism. Based on the results of the analysis of the results, it can be concluded that the Take and Give learning model that is applied to increase self-confidence in learning on the theme of caring for living things, class 1-A at SD Negeri Wonokusumo VI / 45 Surabaya is very effective and highly recommended by the author to continue. developed and implemented following the situation, conditions and atmosphere of student learning so that the teaching and learning process always gets its own appreciation and interest for students.